Optimization of the solar cell based on cadmium telluride by adding the CdSeTe absorbing layer (heterostructure simulation) - Ilchuk, Hryhorii; Semkiv, Ihor; Karkulovska, Maryana; Vashchynskyi, Vitalii; Solovyov, Mykola (Eastern-European Journal of Enterprise Technologies, 2024)
Cadmium telluride solar cells are among the most common devices for photovoltaic applications. However, the energy conversion efficiency of these elements remains insufficiently high. Using the SCAPS programming environment, research and optimization of a classical thin-film solar cell based on CdTe were carried out. The structure of this element consisted of ITO as a transparent conductive contact, a cadmium sulfide (CdS) layer, and a cadmium telluride (CdTe) absorber layer with a metal contact. To optimize this structure in terms of power conversion efficiency, the influence of the thickness and concentration of acceptor impurities in the CdTe absorbing layer, as well as the influence of the thickness and concentration of donor impurities in the CdS buffer layer, were considered. It was established that the optimal thicknesses for the CdS buffer layer and absorption CdTe layers are 50 nm and 3000 nm, respectively. An additional CdSeTe layer between the CdS and CdTe layers has been proposed as one of the optimization options to improve the device efficiency. The main photovoltaic parameters of such a solar cell were analyzed depending on the thickness of the CdSeTe layer and its selenium content. It has been demonstrated that adding CdSeTe solid solution to the 1500 nm thick CdTe absorber layer increases the efficiency of the solar cell by 6.84 %. The main photovoltaic characteristics of CdS/CdTe and CdS/CdSeTe/CdTe solar cells were compared. The results showed that the simulated CdS/CdSeTe/CdTe structure provides better photoconversion efficiency in the AM1.5G light spectrum compared to the classical CdS/CdTe structure. Such elements can be used to form highly efficient solar panels